1995
DOI: 10.1159/000106946
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Changes, Compulsions and Sexual Behavior in Frontotemporal Degeneration

Abstract: The occurrence of weight gain, sweet and carbohydrate craving, hyposexuality, and compulsions in frontal lobe dementia (FLD) compared to Alzheimer’s disease (AD) was evaluated. FLD is a progressive dementia with a high rate of misdiagnosis and therefore better diagnostic criteria for FLD are needed. Fourteen patients meeting research criteria for AD were compared to 14 with suspected FLD. All had cerebral perfusion measured with xenon-133 and imaged with HMPAO using brain-dedicated SPECT. The FLD group showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
3
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 16 publications
3
116
3
5
Order By: Relevance
“…53,54 Interestingly, previous research showed that frontotemporal dementia is associated with changes in eating behaviour including alterations in appetite, food preferences and eating habits (e.g., overeating). 55,56 In spite of the generally higher reactivity of the amygdala in individuals with depression 22 and enhanced amygdala activity in participants with AN when looking at the other woman's body in the present study, we found no differences in amygdala activity between participants with and without depression in the eating-disordered group when either viewing one's own or the other woman's body. Furthermore, in contrast to our hypotheses, we did not find any group difference in the extrastriate body area, 17 either when looking at photographs of one's own body or the other woman's body.…”
Section: Discussioncontrasting
confidence: 77%
“…53,54 Interestingly, previous research showed that frontotemporal dementia is associated with changes in eating behaviour including alterations in appetite, food preferences and eating habits (e.g., overeating). 55,56 In spite of the generally higher reactivity of the amygdala in individuals with depression 22 and enhanced amygdala activity in participants with AN when looking at the other woman's body in the present study, we found no differences in amygdala activity between participants with and without depression in the eating-disordered group when either viewing one's own or the other woman's body. Furthermore, in contrast to our hypotheses, we did not find any group difference in the extrastriate body area, 17 either when looking at photographs of one's own body or the other woman's body.…”
Section: Discussioncontrasting
confidence: 77%
“…This difference may be due to the fact that these studies used retrospective case note review looking for documentation of hypersexual behavior and did not look for evidence of hyposexual behavior. It is notable that the one previous study which included caregiver interviews also found hyposexual behavior in the majority of bvFTD patients [13]. It may be that the emergence of aberrant and disinhibited sexual behaviors are more salient and disruptive to the caregiver in everyday life and thus overshadow the presence of hyposexual behaviors.…”
Section: Discussionmentioning
confidence: 77%
“…As mentioned, one previous study has alluded to the presence of hyposexual behavior in FTD, with 54% of FTD caregivers reporting hyposexual behavior versus 23% in AD patients, and suggested that this may represent one of the first presenting symptoms of FTD [13]. Other studies have reported the rate of sexual changes in AD between 60-80% [28,29] without changes in expression of affection [14].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Miller et al (1995), em estudo que envolveu uma avaliação neuropsicológica ampla, destacaram que os sintomas mais prevalentes no grupo com DFTvc quando comparados ao grupo com DA foram perda de autoconsciência, hiperoralidade, comportamentos estereotipados e perseverantes, redução progressiva da fala, e preservação de orientação espacial. subgrupos da DLFT, a maior sobrecarga emocional esteve associada aos cuidadores de pacientes com DFTvc, em virtude dos distúrbios de comportamento e personalidade, medidos por meio da escala NPI.…”
Section: Sintomas Neuropsiquiátricos Em Pacientes Com Demência Frontounclassified